ANALISIS LAPORAN KEUANGAN OLEH MAHASISWA PROGRAM STUDI AKUNTANSI PADA UMKM PATUNG GYPSUM - Duwi Lestari; Rafif Putra Wiryamanta, Maurheen Queena Hamada, Silvi Kurnia, Ikhsani Fajrul Mubarok, Sri Rahayuning (CV. ADIBA AISHA AMIRA, 2024)
Small and medium-sized enterprises (SMEs) are a type of enterprise that can contribute and play a real role in the economic sector of a country. Many UMKM entrepreneurs manage their without having the knowledge or skills of good business management and finance. One of them at the UMKM Gypsum Statue who has never made a record of financial statements for his business. This type of research is qualitative research. Data sources are obtained from interviews and observations. The results of the research are known that the financial report on UMKM is still simple by carrying out the registration of transactions that often occur in the business and SAK is still not understood by the perpetrators of UMKM. The suggestion from the results of this study is that UMKM should carry out monthly or periodic financial records. In addition, we also suggest that UMKM Gypsum Statue use social media as a means of promotion to increase sales